Skeletal myofiber VEGF deficiency leads to mitochondrial, structural, and contractile alterations in mouse diaphragm - Cannon, Daniel T. (J Appl Physiol (1985), 2019)
Diaphragm dysfunction accompanies cardiopulmonary disease and impaired oxygen delivery. Vascular endothelial growth factor (VEGF) regulates oxygen delivery through angiogenesis, capillary maintenance, and contraction-induced perfusion. We hypothesized that myofiber-specific VEGF deficiency contributes to diaphragm weakness and fatigability. Diaphragm protein expression, capillarity and fiber morphology, mitochondrial respiration and hydrogen peroxide (H(2)O(2)) generation, and contractile function were compared between adult mice with conditional gene ablation of skeletal myofiber VEGF (SkmVEGF(−/−); n = 12) and littermate controls (n = 13). Diaphragm VEGF protein was ~50% lower in SkmVEGF(−/−) than littermate controls (1.45 ± 0.65 vs. 3.04 ± 1.41 pg/total protein; P = 0.001). This was accompanied by an ~15% impairment in maximal isometric specific force (F[1,23] = 15.01, P = 0.001) and a trend for improved fatigue resistance (P = 0.053). Mean fiber cross-sectional area and type I fiber cross-sectional area were lower in SkmVEGF(−/−) by ~40% and ~25% (P < 0.05). Capillary-to-fiber ratio was also lower in SkmVEGF(−/−) by ~40% (P < 0.05), and thus capillary density was not different. Sarcomeric actin expression was ~30% lower in SkmVEGF(−/−) (P < 0.05), whereas myosin heavy chain and MAFbx were similar (measured via immunoblot). Mitochondrial respiration, citrate synthase activity, PGC-1α, and hypoxia-inducible factor 1α were not different in SkmVEGF(−/−) (P > 0.05). However, mitochondrial-derived reactive oxygen species (ROS) flux was lower in SkmVEGF(−/−) (P = 0.0003). In conclusion, myofiber-specific VEGF gene deletion resulted in a lower capillary-to-fiber ratio, type I fiber atrophy, actin loss, and contractile dysfunction in the diaphragm. In contrast, mitochondrial respiratory function was preserved alongside lower ROS generation, which may play a compensatory role to preserve fatigue resistance in the diaphragm. NEW & NOTEWORTHY Diaphragm weakness is a hallmark of diseases in which oxygen delivery is compromised. Vascular endothelial growth factor (VEGF) modulates muscle perfusion; however, it remains unclear whether VEGF deficiency contributes to the onset of diaphragm dysfunction. Conditional skeletal myofiber VEGF gene ablation impaired diaphragm contractile function and resulted in type I fiber atrophy, a lower number of capillaries per fiber, and contractile protein content. Mitochondrial function was similar and reactive oxygen species flux was lower. Diaphragm VEGF deficiency may contribute to the onset of respiratory muscle weakness.